Chromosome polymorphism of heterochromatin and nucleolar regions in two populations of the fish Astyanax bockmanni (Teleostei: Characiformes) - Hashimoto, Diogo Teruo [UNESP]; Porto-Foresti, Fábio [UNESP] (Soc Brasileira Ictiologia, 2010)
Karyotype and other chromosomal markers as revealed by C-banding and silver (Ag) impregnation in two Astyanax bockmanni populations (Barra Seca Stream and Campo Novo River) were examined. The diploid chromosome number 2n = 50 and nearly identical karyotypes were documented. C-banding revealed heterochromatic blocks on the terminal regions of some chromosomes, with high frequencies of polymorphisms. The Ag-impregnation showed that the nucleolus organizer regions (NORs) varied in number, location and organization. Astyanax bockmanni revealed chromosome characteristics similar those of the species complex A. scabripinnis. Mechanisms that may be responsible for the high degree of polymorphism are discussed.

Cariótipo e outros marcadores cromossômicos revelados pelo bandamento C e impregnação da prata (Ag) em duas populações de Astyanax bockmanni (córrego Barra Seca e rio Campo Novo) foram examinados. O número cromossômico diploide 2n = 50 e cariótipo quase idênticos são documentados. Bandamento C revelou blocos heterocromáticos na região terminal de alguns cromossomos, com um elevado nível de polimorfismos. A impregnação da prata mostrou variabilidade do número, posição e organização para as regiões organizadoras de nucléolo (RONs). Astyanax bockmanni revelou características cromossômicas similares ao complexo "A. scabripinnis" e os mecanismos responsáveis pelo alto nível do polimorfismo foram discutidos.
Keywords: Fish cytogenetics; Chromosomal rearrangements; Karyotype differentiation